Metode Moss Art Bryophyta untuk Pembelajaran Biologi Sekolah Menengah Pertama - Eldes Dafrita, Ivan; Trisianawati, Eka; Sari, Mustika; Herditiya, Herditiya; Manisa, Tesa; Nawawi, Nawawi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Based on interviews with the Principal of SMP Negeri 2, Sungai Kakap District, Kubu Raya Regency, several pieces of information were obtained that (1) biology teachers in schools have not optimally utilized natural resources in the form of the diversity of Bryophyta around them as learning resources and (2) there is a lack of skills for students in managing the potential of natural resources around them into learning resources and marketable products. The Community Service Program (PkM) aims to train students to utilize the diversity of Bryophyta by making moss art for students of SMP Negeri 2 Sungai Rengas due to its aesthetic value. The PkM activity was conducted through training and assistance in making moss art for students. During the activity, the students who participated in the training seemed very enthusiastic in listening and following the instructions given and also obtained interesting and varied Moss Art designs from each group. The results of Moss Art-making activities can become one of the internalized activities in the development of the Pancasila Student Project at SMP Negeri 2, Sungai Kakap District, Kubu Raya Regency. The implications of this service are 1) making moss art can be used to strengthen the profile of Pancasila students in implementing the independent curriculum in schools, and 2) teachers can integrate Moss Art making into Biology learning on lower-level plant classification material.